Analysis of Digital Accounting System Implementation, Internal Control, and Tax Compliance on MSME Sustainability in Karawang - Lanjarsih, Laela; Nugrahanti, Trinandari Prasetya; Akbar, Taufiq (West Science Accounting and Finance, 2024)
This study investigates the impact of digital accounting system implementation, internal control effectiveness, and tax compliance on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Karawang. Employing a mixed-methods approach, the research integrates quantitative data from 200 MSMEs across various sectors with qualitative insights from semi-structured interviews. Quantitative analysis reveals significant positive relationships between the adoption of digital accounting systems, the effectiveness of internal controls, and tax compliance with the sustainability of MSMEs. Regression analysis further confirms these factors as significant predictors of business sustainability. Qualitative findings elucidate the challenges and benefits perceived by MSMEs, highlighting barriers such as high initial costs, complexity of technology adoption, and the burden of tax compliance. The study underscores the necessity of supportive policies and programs to enhance MSMEs' capacities in these areas, thereby promoting sustainable business practices and economic stability. This research contributes to the understanding of operational enhancements that drive MSME sustainability and offers actionable insights for stakeholders to foster an enabling environment for MSME growth.